UNRAVELING THE LOCAL FOLK DANCES IN MARINDUQUE - LABAGUIS, GENIL; ASUNCION, REX EMMANUEL (International Journal of Arts, Sciences and Education, 2022)
Folkloric dance is a significant part of the cultural heritage in the island province of Marinduque, which signifies the values, norms, customs, and traditions of the native people. The dance movements, props, and costumes used imply how folks live and show the status of the economic industry in the past decades. This research study aimed to explore the existence of folkloric dances as the basis for curriculum enhancements in Physical Education by the Department of Education (DepEd). A descriptive research design was employed. There were ten (10) folk dances identified. These folkloric dances in the island province of Marinduque were documented and almost completely notated through simplified piano arrangements. Most of the dances do not specifically identify particular props, aside from Igiban sa Nayon, Cachucha de Banuyo, and Sulong Aking Tandang from the Municipilty of Gasan and Bila-bila. The costumes for females are commonly baro, saya, kimona, and Maria Clara, while for males, the Camisa de Chino, Barong Tagalog, colored trousers, and black pants. The output of this research study aligned and served as the basis for the curriculum enhancement of the Department of Education (DepEd), especially in the physical education subjects of grades 4, 5, 6, 7, 8, and 12. Integration into the Bachelor of Culture and Arts Education (BCAEd) program is also a possibility.